2019
DOI: 10.1002/pmic.201800167
|View full text |Cite
|
Sign up to set email alerts
|

Protein Composition Reflects Extracellular Vesicle Heterogeneity

Abstract: Extracellular vesicles (EVs) are membrane‐enclosed particles that are released by virtually all cells from all living organisms. EVs shuttle biologically active cargo including protein, RNA, and DNA between cells. When shed by cancer cells, they function as potent intercellular messangers with important functional consequences. Cells produce a diverse spectrum of EVs, spanning from small vesicles of 40–150 nm in diameter, to large vesicles up to 10 μm in diameter. While this diversity was initially considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 75 publications
2
73
0
Order By: Relevance
“…While different types of mechanisms have been proposed for exosome uptake, it is known that exosomes interact with the recipient cell, and transmit information resulting in changes in surrounding cells via (1) direct stimulation by membrane ligands; (2) receptor transfer between the donor cells and recipient cells; (3) transfer of genetic information; and (4) direct stimulation by endocytically-expressed surface receptors in recipient target cells [16]. Recently, a thorough description of their protein composition has led to an improved classification of EVs [17].…”
Section: Exosomesmentioning
confidence: 99%
“…While different types of mechanisms have been proposed for exosome uptake, it is known that exosomes interact with the recipient cell, and transmit information resulting in changes in surrounding cells via (1) direct stimulation by membrane ligands; (2) receptor transfer between the donor cells and recipient cells; (3) transfer of genetic information; and (4) direct stimulation by endocytically-expressed surface receptors in recipient target cells [16]. Recently, a thorough description of their protein composition has led to an improved classification of EVs [17].…”
Section: Exosomesmentioning
confidence: 99%
“…As PADs have been identified to be a key regulator of extracellular (EV)-release, a mechanism that has been found to be phylogenetically conserved from bacteria to mammals (Kholia et al, 2015;Kosgodage et al, 2017Kosgodage et al, , 2018Gavinho et al, 2019;Kosgodage et al, 2019), the characterisation of EVs in camelids is of further interest. Extracellular vesicles (EVs) are found in most body fluids and participate in cellular communication via transfer of cargo proteins and genetic material (Inal et al, 2013;Colombo et al, 2014;Lange et al, 2017;Turchinovich et al, 2019;Vagner et al, 2019). EVs in body fluids, including serum, can also be useful biomarkers to reflect health status (Hessvik and Llorente, 2018;Ramirez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…EVs possess a diverse collection of proteomic cargo (Greening et al, 2017;Vagner et al, 2019) that changes dynamically according to cell state and environmental conditions. For instance, Kreger et al (2016) found that transformation of mouse embryonic fibroblasts with an oncogenic form of diffuse B cell lymphoma (onco-Dbl) both increased the rate of microvesicle production, as well as altered their proteomic contents.…”
Section: Proteomic Content and Cargo Sortingmentioning
confidence: 99%